THE INFLUENCE OF INSTRUMENTAL MUSIC RELAXATION TECHNIQUES ON THE ANXIETY OF 3RD TRIMESTER PREGNANT WOMEN AT TPMB NINING KARAWANG DISTRICT IN 2023 - Mustafa, Ayu Resky; Masitoh, Imas (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: According to data from the World Health Organization, every day around 810 women die during pregnancy or childbirth due to preventable causes. Maternal mortality is still very high today. Around 295 thousand women die before or during childbirth and 86% occur in developing countries. The 2022 Performance Report of the Directorate of Nutrition and Maternal and Child Health shows a significant decline, even much lower than the 2022 target of 205 deaths per 100,000 live births. Objective: to find out the Effect of Instrumental Music Relaxation Techniques on the Anxiety of Pregnant Women in the Third Trimester at TPMB Nining 2023. Method : This type of research is pre-experimental quantitative research with a one group Pretest Posttest design. Some of the population in this study is a population of less than 100. So the number of samples in this study is 30 pregnant women in the third trimester of pregnancy. The sampling technique uses techniquesTotal sampling. Results: Wilcoxon test significance value 0.001 <0.05, then H 0 was rejected so it was concluded that there was an effect of providing instrumental music relaxation on the anxiety of pregnant women in the third trimester at TPMB Nining, Karawang Regency in 2023. Conclusion: There is an Influence of Instrumental Music Relaxation Techniques on the Anxiety of Pregnant Women in the Third Trimester at TPMB Nining, Karawang Regency in 2023. Suggestion : It is hoped that this research can become a source of knowledge for the public regarding instrumental music relaxation techniques to reduce anxiety for pregnant women in the third trimester.